2014
DOI: 10.1038/mp.2014.114
|View full text |Cite
|
Sign up to set email alerts
|

Vascular hippocampal plasticity after aerobic exercise in older adults

Abstract: Aerobic exercise in young adults can induce vascular plasticity in the hippocampus, a critical region for recall and recognition memory. In a mechanistic proof-of-concept intervention over 3 months, we investigated whether healthy older adults (60-77 years) also show such plasticity. Regional cerebral blood flow (rCBF) and volume (rCBV) were measured with gadolinium-based perfusion imaging (3 Tesla magnetic resonance image (MRI)). Hippocampal volumes were assessed by high-resolution 7 Tesla MRI. Fitness improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
355
7
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 318 publications
(388 citation statements)
references
References 50 publications
21
355
7
5
Order By: Relevance
“…Interestingly, neither baseline CRF nor change in CRF was related to hippocampal volume in the cognitively healthy participants of either study (Honea et al., 2009; Vidoni et al., 2012). More recently, change in CRF following an exercise intervention has been positively associated with hippocampal head volume (Maass et al., 2015) and hippocampal tissue density (Kleemeyer et al., 2015) in cognitively healthy older adults. Overall, current research demonstrates inconsistent associations between CRF and hippocampal volume.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, neither baseline CRF nor change in CRF was related to hippocampal volume in the cognitively healthy participants of either study (Honea et al., 2009; Vidoni et al., 2012). More recently, change in CRF following an exercise intervention has been positively associated with hippocampal head volume (Maass et al., 2015) and hippocampal tissue density (Kleemeyer et al., 2015) in cognitively healthy older adults. Overall, current research demonstrates inconsistent associations between CRF and hippocampal volume.…”
Section: Discussionmentioning
confidence: 99%
“…In older adults, large‐scale cross‐sectional studies have reported contradictory associations. Positive associations between CRF/physical activity and RAVLT performance have been reported (Boots et al., 2014; Pizzie et al., 2014; Zhu et al., 2014) while others studies did not observe such associations (Maass et al., 2015; Varma et al., 2015). Randomized controlled trials provide evidence that aerobic exercise (Klusmann et al., 2010) and resistance exercise (Cassilhas et al., 2007) training can improve episodic memory in cognitively healthy older adults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This increase in blood flow appears to aid in earlier recall for complex spatial objects. 8,9 Further, in elderly subjects, 6 months of aerobic training has been shown to mitigate age-related decline in both verbal and spatial memory, 10 while a low activity, 8-week yoga intervention significantly improved performance on task switching, working memory, and the n-back task. 11 In young males, high-intensity cycling has been associated with better acquisition and retention 7 days later on the visuomotor tracking task.…”
Section: Animal Models Of Exercisementioning
confidence: 98%